2013
DOI: 10.1016/j.gca.2012.10.027
|View full text |Cite
|
Sign up to set email alerts
|

Ab initio molecular dynamics simulation and free energy exploration of copper(I) complexation by chloride and bisulfide in hydrothermal fluids

Abstract: Ab initio molecular dynamics simulation and free energy exploration of copper(I) complexation by chloride and bisulfide in hydrothermal fluids Geochimica et Cosmochimica Acta, 2013; 102:45-64 © 2012 Elsevier Ltd. All rights reserved. NOTICE: this is the author's version of a work that was accepted for publication in Geochimica et Cosmochimica Acta. Changes resulting from the publishing process, such as peer review, editing, corrections, structural formatting, and other quality control mechanisms may not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
74
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(75 citation statements)
references
References 82 publications
1
74
0
Order By: Relevance
“…This raises the possibility that the coordination of halide ions may favor one coordination geometry (i.e., square antiprism) versus another (tri-capped trigonal prismatic) for the aquo ion at room temperature; this geometric effect may contribute to further decreasing the overall coordination number. We also note that such coordination changes are associated with large entropy changes because of the release of free water molecules, and hence are strongly temperature-dependent (e.g., Sherman, 2010; Mei et al, 2013). Ohoa et al (2015) performed in-situ 139 La NMR spectroscopy at room temperature up to pressures of 16 kbar (i.e., in metastable water).…”
Section: Speciesmentioning
confidence: 86%
See 1 more Smart Citation
“…This raises the possibility that the coordination of halide ions may favor one coordination geometry (i.e., square antiprism) versus another (tri-capped trigonal prismatic) for the aquo ion at room temperature; this geometric effect may contribute to further decreasing the overall coordination number. We also note that such coordination changes are associated with large entropy changes because of the release of free water molecules, and hence are strongly temperature-dependent (e.g., Sherman, 2010; Mei et al, 2013). Ohoa et al (2015) performed in-situ 139 La NMR spectroscopy at room temperature up to pressures of 16 kbar (i.e., in metastable water).…”
Section: Speciesmentioning
confidence: 86%
“…For higher temperature, our understanding of its behavior, until recently, has been limited to the theoretical study of Sverjensky (1984), which predicted that Eu 2+ would be favored over Eu 3+ with increasing temperature, and the study of Haas et al (1995) who reported formation constants for Eu(II) chloride complexes based on the data for chloride complexes of divalent transitions metals. These data however, have been largely superseded by a variety of recent experimental data (e.g., Testemale et al, 2009;Mei et al, 2013), raising questions about reliability of earlier predictions of the stability of Eu 2+ complexes. The XAS study of Liu et al (2016) provided the first experimental confirmation of the increase in the stability of Eu 2+ over Eu 3+ with increasing temperature predicted by Sverjensky (1984), and demonstrated that Eu(II) is the prevalent oxidation state for Eu in most crustal fluids at temperatures ≥200°C (Fig.…”
Section: Stability Of Ce(iv) and Eu(ii) Species In Hydrothermal Solutmentioning
confidence: 99%
“…The presented thermodynamic calculations suggest that the Pokrovski et al 2008;Zajacz and Halter 2009;Zajacz et al 2011;Blundy et al 2015). Although high Cu solubility in a magmatic aqueous vapour phase is under discussion (Lerchbaumer and Audétat 2012), experimental studies have shown that mixed ligand complexes including S and Cl are the most stable Cu complexes (e.g., CuCl(HS) − ) representing the most efficient form to transport Cu in magmatic volatiles (Simon et al 2006;Mei et al 2013). Such a magmatic volatile phase can contribute Cu and other chalcophile metals to an overlying hydrothermal system, which can result in high concentrations of these metals in the seafloor massive sulphides (de Ronde et al 2005;Berkenbosch et al 2012;Gruen et al 2014).…”
Section: Formation Of Magmatic Sulphides and Their Potential Role As mentioning
confidence: 96%
“…Sherman (2011) 10. Bourcier and Barnes (1987); Tagirov and Seward (2010); Mei et al (2013) Especially in the last few decades, there have been major improvements in powerful theories that can identify the structures and relative stabilities of aqueous complexes through modelling . The Pearson correlations have been supplanted by these much more powerful means of evaluating the stoichiometries and stabilities of hydrothermal complexes .…”
Section: Metal Complexes Referencesmentioning
confidence: 99%